Challenges and opportunities in insomnia disorder. (2nd November 2021) - Roach, Meaghan; Juday, Timothy; Tuly, Rifat; Chou, Jacquelyn W.; Jena, Anupam B.; Doghramji, Paul P.
Abstract: Background: Insomnia disorder is a prevalent, often unrecognized condition that affects millions. This clinical disorder is characterized by difficulty initiating or maintaining sleep over a sustained period. In fact, insomnia disorder affects much more than sleep; it increases the risk of developing serious medical and psychiatric comorbidities and can exacerbate existing conditions. The association between insomnia disorder and serious medical and psychiatric comorbidities are complex and directionality is not yet fully understood. There remain gaps in the treatment landscape for insomnia disorder. Methods: We performed a narrative review of the published literature to identify challenges, unmet needs, and burden associated with insomnia disorder. Results: In this article, we describe the substantial burden that insomnia disorder poses on patients, the healthcare system, and society in the US. This article explores the factors attributable to this burden including limited provider knowledge, inadequate treatment options, and unknown long-term impacts of off-label treatments. Conclusions: Several recommendations are proposed to address these challenges and improve patient outcomes through efforts to: (1) establish the societal value of treatment; (2) improve the clinical understanding of insomnia disorder; and (3) prioritize development of and access to effective treatments that do not pose addiction potential or tolerability issues.